Perceived Ageism During the Covid-19-Crisis Is Longitudinally Related to Subjective Perceptions of Aging - Kornadt, Anna E.; Albert, Isabelle; Hoffmann, Martine; Murdock, Elke; Nell, Josepha (Frontiers in Public Health, 2021)
Ageism in media and society has increased sharply during the Covid-19-crisis, with expected negative consequences for the health and well-being of older adults. The current study investigates whether perceived ageism during the crisis longitudinally affects how people perceive their own aging. In June 2020, N = 611 older adults from Luxembourg [aged 60 – 98 years, Mage(SD) = 69.92(6.97)] participated in a survey on their perception of the crisis. In October 2020, N = 523 participated in a second measurement occasion. Participants reported on perceived ageism during the crisis in different domains, their self-perceptions of aging and subjective age. In latent longitudinal regression models, we predicted views on aging at T2 with perceived ageism at T1, while controlling for baseline views on aging and covariates. Perceived ageism at T1 increased self-perceptions of aging as social loss and yielded a trend for physical decline, while there were no effects on subjective age and self-perceptions of aging as continued growth. Views on aging are powerful predictors of well-being and health outcomes in later life. Our data suggest that being the target of ageism during the crisis negatively affects older adults’ self-perceptions of aging and this impact may be felt beyond the current crisis.